The origin of in-vitro estrogen-like activity in oregano herb extracts. (April 2019) - Wielogorska, Ewa; Blaszczyk, Katarzyna; Chevallier, Olivier; Connolly, Lisa
Abstract: Global market of herbs has been struggling with food adulteration issues. A number of assays have been developed to aid the detection of the tampered samples and ensure high quality of the marketed products. However, herbs are marketed not only for their culinary applications but also as remedies due to high levels of biologically active constituents. Nevertheless, there is no information in the literature about the influence of herbs adulteration on the biological activity of the final product. Current study aims at assessing the influence of oregano adulteration on its in-vitro estrogen-like activity. High responses in a mammalian reporter gene assay have been detected in pure and adulterated samples, translating to 21–7409 ng of 17β-estradiol equivalents per gram of oregano. The origin of those responses was assessed by combining fractionation and UHPLC-HRMS. Three flavones were proposed as the most active extract constituents i.e. luteolin-glucoside, luteolin- and apigenin-glucuronides all of which have been previously identified in other herbal extracts with estrogenic activity. This study underlines challenges of biological activity assessment in complex herbal extracts as well as the need for further assessment of such supplement administrations in the case of postmenopausal women and breast cancer patients undergoing hormone therapy. Highlights: Oregano extracts exhibit estrogen-like activity in-vitro . Conjugated flavonoids are the origin of the detected biological activity. Combining bio- and chemical assays is a fast tool for detecting bioactive compounds.